2017
DOI: 10.1021/acs.jproteome.7b00541
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Reaction Monitoring for the Quantitation of Serum Protein Glycosylation Profiles: Application to Ovarian Cancer

Abstract: Ascites fluid is present in over 30% of diagnosed ovarian cancer (OC) cases and is produced when tumor cells metastasize into the peritoneal cavity. Because of increased interest in the immune status of ovarian cancer patients who present with metastatic ascites and the potential role that glycosylation plays with functions of the different immunoglobulins such as complement-dependent and antibody-dependent cytotoxicity largely through the activity of Fc receptors. Immunoglobulins IgA and IgG were affinity iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 69 publications
2
40
0
Order By: Relevance
“…ORM1 is an acute phase protein in humans and mice with inflammatory and immunomodulatory properties, the serum concentration of which rises two to five times during an acute phase response . Increasing expression of ORM1 has been reported to be used as a biomarker in various advanced cancers, such as bladder cancer , ovarian cancer and lung cancer , in studies that have focused on analysing late‐stage serum and urine samples with mass spectrometry. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORM1 is an acute phase protein in humans and mice with inflammatory and immunomodulatory properties, the serum concentration of which rises two to five times during an acute phase response . Increasing expression of ORM1 has been reported to be used as a biomarker in various advanced cancers, such as bladder cancer , ovarian cancer and lung cancer , in studies that have focused on analysing late‐stage serum and urine samples with mass spectrometry. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…ORM1 is an acute phase protein in humans and mice with inflammatory and immunomodulatory properties, the serum concentration of which rises two to five times during an acute phase response [34,35]. Increasing expression of ORM1 has been reported to be used as a biomarker in various advanced cancers, such as bladder cancer [23], ovarian cancer [36] and lung cancer [37], in studies that have focused on analysing late-stage serum and urine samples with mass spectrometry. Zhang et al [38] previously identified that increased ORM1 acts as an early-detection protein biomarker of lung cancer in urine samples in KRas-driven lung cancer mouse models, which was validated in 16 human cancer urine samples and in tumour-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of TFN glycoforms is commonly carried out at the glycopeptide level by triple quadrupole MRM experiments. 48,49 Compared to these methods, our method showed similar performances in terms of detection limits (ranging from 0.5 to 0.9 µg mL −1 ), precision, accuracy, and linearity. An example of quantification of TFN at the intact protein level was performed by LC-ICP-MS, focusing on the different sialoforms present on the protein.…”
Section: Discussionmentioning
confidence: 86%
“…Due to the importance of protein glycosylation in biological systems, glycoproteomics has been extensively applied to disease-related research (Whelan et al, 2009;Hwang et al, 2010;Song et al, 2014;Reiding et al, 2017;Yang et al, 2017b;Kailemia et al, 2018), such as hepatitis, cancer (Dai et al, 2011;Liu et al, 2014;Kailemia et al, 2017;Miyamoto et al, 2018;Veillon et al, 2018), and infectious diseases (Vigerust, 2011;Go et al, 2017). Glycosylation can change chemical and physical properties of proteins, and regulate their binding and interactions with ligands or extracellular matrix.…”
Section: E Clinical Samplesmentioning
confidence: 99%